2023
DOI: 10.5435/jaaos-d-22-00838
|View full text |Cite
|
Sign up to set email alerts
|

Few Randomized Controlled Trials in Spine Surgery in the United States Include Sociodemographic Patient Data: A Systematic Review

Abstract: Introduction:The importance of sociodemographic factors such as race, education, and income on spine surgery outcomes has been well established, yet the representation of sociodemographic data within randomized controlled trials (RCTs) in spine literature remains undefined in the United States (U.S). Methods: Medical literature was reviewed within PubMed for RCTs with "spine" in the title or abstract published within the last 8 years (2014 to 2021) in seven major spine journals. This yielded 128 results, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A 2023 study by Kirchner et al. 9 found race and ethnicity to be reported in 37% and 27.8% respectively of spine surgery RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2023 study by Kirchner et al. 9 found race and ethnicity to be reported in 37% and 27.8% respectively of spine surgery RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, studies also have shown that these variables have been drastically under-reported in randomized controlled trials (RCTs) across many medical and surgical specialties, 6 , 7 , 8 including orthopaedic RCTs. 9 , 10 , 11 …”
mentioning
confidence: 99%